The Role of N-Acetyl-Aspartyl-Glutamate (NAAG) in the Modulation of NMDA Receptors - Khacho, Pamela (Université d'Ottawa / University of Ottawa, 2016)
Ischemic strokes cause excessive release of glutamate, leading to overactivation of N-methyl-D-aspartate receptors (NMDARs) and excitotoxicity-induced neuronal death. For this reason, inhibition of NMDARs has been a central focus in identifying mechanisms to avert this extensive neuronal damage. N-acetyl-aspartyl-glutamate (NAAG), the most abundant neuropeptide in the brain, is neuroprotective in ischemic conditions in vivo. Despite this evidence, the exact mechanism underlying its neuroprotection, and more specifically its effect on NMDARs, is currently unknown due to conflicting results in the literature. Here, we uncover a pH-dependent and subunit specific action of NAAG on NMDARs. Using whole-cell electrophysiological recordings on acute hippocampal slices from adult mice and on HEK293 cells, we found that NAAG increases synaptic GluN2A-containing NMDAR excitatory postsynaptic currents (EPSCs), while effectively decreasing extrasynaptic GluN2B-containing NMDAR EPSCs in physiological pH. Intriguingly, the results of our study further show that in low pH, which is a physiological occurrence during ischemia, NAAG depresses GluN2A-containing NMDAR EPSCs and amplifies its inhibitory effect on GluN2B-containing NMDAR EPSCs, as well as upregulates the surface expression of the GluN2A subunit. Altogether, our data demonstrate that NAAG has differential effects on NMDAR function based on subunit composition and extracellular pH levels. These findings suggest that the role of NAAG as a neuroprotective agent during an ischemic stroke is likely mediated by its ability to reduce NMDAR excitation. The inhibitory effect of NAAG on NMDARs and its enhanced function in acidic conditions makes NAAG a prime therapeutic agent for the treatment of ischemic events.
Keywords: N-acetyl-aspartyl-glutamate (NAAG); NMDA receptors; Protons; Neuroprotection; Hippocampus; Electrophysiology